2018
DOI: 10.1097/pts.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Korean Version of the Second Victim Experience and Support Tool (K-SVEST)

Abstract: Objectives “Second victims” are defined as healthcare professionals whose wellness is influenced by adverse clinical events. The Second Victim Experience and Support Tool (SVEST) was used to measure the second-victim experience and quality of support resources. Although the reliability and validity of the original SVEST have been validated, those for the Korean tool have not been validated. The aim of the study was to evaluate the psychometric properties of the Korean version of the SVEST. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
116
9
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(153 citation statements)
references
References 26 publications
24
116
9
4
Order By: Relevance
“…Therefore, item N10, N15, N16 and N17 were added to the C‐SVEST scale. In this study, the Cronbach's α coefficients of colleague support were 0.713, which is higher than the findings which were 0.61 in the original version (Burlison et al, ), 0.63 in the Korean version (Kim et al, ), and 0.56 in the Argentina version (Brunelli et al, ), which showed similar results in institutional support.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Therefore, item N10, N15, N16 and N17 were added to the C‐SVEST scale. In this study, the Cronbach's α coefficients of colleague support were 0.713, which is higher than the findings which were 0.61 in the original version (Burlison et al, ), 0.63 in the Korean version (Kim et al, ), and 0.56 in the Argentina version (Brunelli et al, ), which showed similar results in institutional support.…”
Section: Resultscontrasting
confidence: 59%
“…Reliability and validity of the SVEST scale were reported in several countries (Brunelli, Estrada, & Celano, ; Burlison et al, ; Kim, Kim, Lee, Burlison, & Oh, ). However, it has not been tested in China.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The patient safety culture has a positive impact on organisational support, and both patient safety culture and organisational support have positive effect in reducing the second victim-related distresses.4 | D ISCUSS I ONPreventing health care providers from becoming the second victim post any adverse events is important since the second victim-related distress could further negatively affect patient safety and turnover intention(Kable et al, 2018;Wu & Steckelberg, 2012). The participants in the current study reported significantly higher percentage in physical and psychological distress and turnover intention compared with the study done in the United States(Burlison, Quillivan, Scott, Johnson, & Hoffman, 2016); however, those second victim-related distresses and their consequences are similar to the results reported by the nurses in Korea(Kim, Kim, Lee, Burlison, & Oh, 2018). The significantly higher distress and turnover intention rate might be associated with the absence of affirmative patient safety culture and organisation support.…”
supporting
confidence: 69%
“…The study findings showed that the RNs scored highest in psychological distress dimension (Table ); therefore, it is very important to assess their psychological status and, further, to assist them to decrease the distress. The researches have shown that support from managers and peers, especially in displays of affection and information, could effectively decrease psychological distress (Kim et al, ; Tamburri, ). Colleague support (1.1%, Table ) was very limited for the participants in the current study; however, the most needed support was a respected colleague with whom to discuss the incident.…”
Section: Discussionmentioning
confidence: 99%